The improvement in respiratory function by inspiratory muscle training is due to structural muscle changes in patients with stroke: a randomized controlled pilot trial. Issue 1 (2nd January 2018) - Cho, Ji-Eun; Lee, Hwang-Jae; Kim, Min-Kyu; Lee, Wan-Hee
Abstract: Background: The changes effected by the inspiratory muscle training (IMT) on the structure of inspiratory muscles such as on the diaphragm, in patients with stroke, is unclear. Objective: To investigate the effect of IMT on inspiratory function, diaphragm thickness, walking endurance, and fatigue in patients with stroke. Methods: A total of 30 patients with stroke were randomized to either the experimental group or the control group. The experimental group ( n = 15) underwent inspiratory muscle training with resistance adjusted to 30% of maximal inspiratory pressure, 90 breaths a day, 5 times a week for 6 weeks. Both groups received regular physical therapy for the same amount of time. The primary outcome measure was the diaphragm thickness ratio. The secondary outcomes were inspiratory function; maximal inspiratory pressure and inspiratory muscle endurance; and gait endurance and fatigue. Results: There were significant differences between the two groups in the thickness ratio on the affected diaphragm thickness (medium effect size), maximal inspiratory pressure (medium effect size), and inspiratory muscle endurance (large effect size; Bonferroni correction p < 0.005). The gait endurance (medium effect size) and fatigue (small effect size) showed no significant differences in the between group comparison. Conclusion: Inspiratory muscle training was effective in improving respiratory function and inducing structural changes, especially in the affected diaphragm.